Interagir avec la « machine » à l'ère du numérique : des représentations des étudiants à l'évaluation de leur performance académique en anglais - Cédric Brudermann
While technology-mediated language learning environments seek to make second language (L2) learners autonomous (as far as possible) in their L2 practices, they paradoxically place them at the center of complex interactions with three external factors which may cause anxiety symptoms: the human-computer interface, the online learning experience and the L2 itself.In this respect, in order to further explore the impact of these variables on the learners' L2 performance in a technology-mediated language learning environment, an exploratory study was conducted during the academic year 2014-2015 among a group of 250 first year STEM (Science, Technology, Engineering and Mathematics) students who were enrolled in an English as a foreign language guided autonomy learning pathway (B1 proficiency level). In this study, three questionnaires were designed (one per potentially anxiety-provoking variable) and submitted to a set of participants (n = 250) at the onset of the academic year in order to know more about their representations concerning the potential of digital learning environments to foster L2 development. Various sets of data (i.e. students' attendance, satisfaction and performance at the ﬁnal examination) were besides collected and analysed at the end of the academic year.A confrontation between the study participants' representations concerning technology-mediated language learning environments and their actual performance in such an environment was thus made possible. Cross-references and comparison of the data revealed that, while the three potentially anxiety-provoking variables explored in this study did not seem to act as a brake on the study participants' L2 learning processes, the online learning environment dealt with in this paper seem to be more relevant to promote L2 skills stabilization than L2 acquisition gains.